Meningkatkan Hasil Belajar Menggunakan Model Problem Based Learning, Course Review Horay, Make a Match Muatan PPKn Kelas V SDN Kuin Utara 7 Banjarmasin - Al Fredi Stiawan; Susilawaty (CV. ITTC INDONESIA, 2023)
The research problem is the low learning outcomes in PPKn theme 7 Events in Life. This is caused by the teacher not involving students in the learning process. Efforts to overcome these problems by applying the Problem Based Learning learning model, Course Review Horay, Make a Match. The purpose of this research is to describe teacher activities, student activities and learning outcomes. This study used Classroom Action Research which was held in 3 meetings. Using qualitative and quantitative approaches. The subjects of this study were fifth grade students at SDN Kuin Utara 7 Banjarmasin, a total of 17 students consisting of 10 male students and 7 female students, semester II of the 2022/2023 academic year. The results of this study showed that student activity at meeting 1 obtained a percentage of 65% including active criteria, the second meeting obtained a percentage of 76% including very active criteria and the third meeting obtained a score of 83% including very active criteria and completeness of classical student learning outcomes at the meeting 1 gets a percentage of 12%, meeting 2 gets a percentage of 29% and meeting 3 gets a percentage of 94% having achieved classical completeness. Learning PPKn Theme 7 Events in Life using the model Problem Based Learning, Course Review Horay, Make a Match is suggested as an alternative to increase teacher activity, student activity and learning outcomes.